Penyuluhan dan Motivasi Kewirausahaan bagi Siswa SMA Al-Ghurabaa Jakarta Timur dalam Menumbuhkan Minat Berwirausaha - Arya Darmawan; Zulkarnaini Zulkarnaini; Meita Pragiwani; Sri Handoko Sakti; Irfan Arif Husen; Farmansyah Maliki (LPMP Imperium, 2026)
Entrepreneurship is a strategic alternative for improving the economic independence of high school graduates in facing limited employment opportunities and the high cost of higher education. This community service activity aimed to increase entrepreneurial literacy and motivation among students of SMA Al-Ghurabaa, East Jakarta. The program was implemented through interactive methods including lectures, discussions, and question-and-answer sessions, supported by real case studies of successful and unsuccessful business practices. The activity was conducted on November 14, 2025, at the SMA Al-Ghurabaa hall and involved active participation from students. The results showed a significant increase in students’ understanding of basic entrepreneurial concepts, business opportunities, and risk awareness. Students also demonstrated higher motivation, creativity, and interest in developing business ideas. This program indicates that structured entrepreneurial counseling can effectively foster students’ readiness to engage in entrepreneurial activities. It is expected that with continuous guidance from teachers and schools, students will be able to develop simple business plans and apply entrepreneurial skills in a sustainable manner.